2020
DOI: 10.1101/2020.04.10.20061176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Stage Group Testing Improves Efficiency of Large-Scale COVID-19 Screening

Abstract: 189Manuscript: 2442 Abstract Background:SARS-CoV-2 test kits are in critical shortage in many countries. This limits large-scale population testing and hinders the effort to identify and isolate infected individuals. Objectives:Herein, we developed and evaluated multi-stage group testing schemes that test samples in groups of various pool sizes in multiple stages. Through this approach, groups of negative samples can be eliminated with a single test, avoiding the need for individual testing and achieving consi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…By this time, 7 (0-25) additional patients and/or staff had acquired COVID-19 but did not (yet) show symptoms. The lag until first onset of severe COVID-19 symptoms was greater (12 days from index case, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and coincided with a greater number of undetected infections (23,.…”
Section: Covid-19 Spreads Quickly But Symptoms Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…By this time, 7 (0-25) additional patients and/or staff had acquired COVID-19 but did not (yet) show symptoms. The lag until first onset of severe COVID-19 symptoms was greater (12 days from index case, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and coincided with a greater number of undetected infections (23,.…”
Section: Covid-19 Spreads Quickly But Symptoms Lagmentioning
confidence: 99%
“…3,[6][7][8] Yet symptomatic cases represent just the tip of the iceberg: infectious individuals with no, mild, or as-yet undeveloped symptoms are common in COVID-19 outbreaks, and can easily go undetected by syndromic surveillance systems while nonetheless seeding chains of transmission. [9][10][11] Recent studies have indicated that surveillance strategies such as group testing may represent effective and resource-efficient alternatives to standard syndromic surveillance, [12][13][14][15] but few settings have adopted such practices.…”
Section: Introductionmentioning
confidence: 99%
“…For an assay with negligible error, a positive test result for a pooled sample would indicate that the molecular alteration is present in one or more subjects in the pool, while a negative test result would indicate the contrary. Since its introduction by Dorfman (8) as a cost-efficient way of screening for syphilis, GT has been applied to many different areas of biomedical research including virology (9-11), genetics (12)(13)(14)(15), drug development (16), and most recently Covid-19 (17)(18)(19). In particular, the feasibility and performance of GT for detecting mutations in tumor have been investigated with promising results (13)(14)(15).…”
Section: Group Testingmentioning
confidence: 99%
“…Pooled testing is a diagnostic approach where samples from multiple patients are combined and analyzed in a single test reaction 7 . If the reaction is positive, then individual samples that contributed to that reaction need to be retested singly ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this strategy has been applied in blood banks to screen blood products for HIV-1, hepatitis B and C viruses 9 , 10 . Now, again, this strategy is finding application in identifying SARS-CoV-2 infected individuals in the ongoing COVID-19 pandemic 7 , 11 15 .…”
Section: Introductionmentioning
confidence: 99%